Bullying victimization and physical fighting among Venezuelan adolescents in Barinas: results from the Global School-Based Health Survey 2003 - Herring Patricia; Rudatsikira Emmanuel; Siziya Seter; Muula Adamson (BMC, 2009)
Abstract Background Violence among adolescents has untoward psycho-social and physical health effects among this age group. Most of the literature on this topic has been from high-income nations, and little information has come from middle- and low-income nations. This study was done to assess the relationship between physical fighting and bullying victimization among Venezuelan school-going adolescents in Barinas. Method We used data from the 2003 Global School-Based Health Survey conducted among in-school adolescents in Barinas, Venezuela. We estimated the prevalence of bullying victimization and physical fighting. We also conducted Logistic regression analysis to assess the association between a selected list of explanatory variables and physical fighting. We hypothesized that there would be a dose-response relationship between physical fighting and number of times the adolescent reported being a bullied in the past 30 days. Results A total of 2,249 adolescent students participated in the survey. However data on sex (gender) were available for only 2,229 respondents, of whom 31.2 (47.4% males and 17.0% females) reported having been involved in a physical fight in the last 12 months. Some 31.5% (37.0% males and 27.0% females) reported having been bullied in the past 30 days. There was a dose-response relationship between bullying victimization and physical fighting (p-trend < 0.001). Compared to subjects who were not bullied, those who reported being bullied were more likely to engage in physical fighting after controlling for age, sex, substance use (smoking, alcohol drinking or drug use), and parental supervision. Conclusion Physical fighting and bullying victimization experience is common among in-school adolescents in Barinas, Venezuela. The fact that victims of bullying were more likely to have engaged in physical fighting may be evidence supporting the notion that "violence begets more violence".